NOSOCOMIAL INFECTIONS IN PATIENTS WITH UROLITHIASIS IN THE POSTOPERATIVE PERIOD - F. S. Sadulloev (Исследования и практика в медицине)
Abstract:Objective: To determine the most frequent causative agents of nosocomial infection in patients with urolithiasis in the postoperative period.Material and Methods. The study is based on the results of comprehensive studies conducted in 122 patients with nosocomial urinary tract infection, detected in 823 patients with urolithiasis treated by various methods. A cohort of 823 patients is isolated from 2688 patients treated without at admission signs of infections in the urinary tract for the period 2011–2014. All patients were treated at the Urological department of Avicenna Tajik State Medical University in the Republican Clinical Center of Urology. Main results. By the method of randomly selected 823 medical records of patients with urolithiasis various operations we carried out with 122 patients revealed cases of nosocomial infections. The diagnosis of nosocomial infections on the basis of established symptomatic urinary tract infection, asymptomatic bacteriuria or the presence of wound infection, use during the hospital stay for treatment of antibiotics, antiseptics, physiotherapy and other therapies. The incidence of nosocomial infections was studied in dependence with the severity of the underlying disease, the volume of surgical, invasive, endoscopic and other urological procedures, the timing and frequency of tests, the proportion of individual clinical manifestations in the overall structure of urinary tract infections, sex and age of patients.Conclusions. The leading microflora causing nosocomial infection in patients with urolithiasis in all treatments are gram-negative microorganisms, including prevailing E.coli (24,0%).